Hypopharyngeal Ulcers in COVID-19: Histopathological and Virological Analyses – A Case Report - Porzionato, Andrea; Stocco, Elena; Emmi, Aron; Contran, Martina; Macchi, Veronica; Riccetti, Silvia; Sinigaglia, Alessandro; Barzon, Luisa; De Caro, Raffaele (Frontiers in Immunology, 2021)
In coronavirus disease 2019 (COVID-19), ulcerative lesions have been episodically reported in various segments of the gastrointestinal (GI) tract, including the oral cavity, oropharynx, esophagus, stomach and bowel. In this report, we describe an autopsy case of a COVID-19 patient who showed two undiagnosed ulcers at the level of the anterior and posterior walls of the hypopharynx. Molecular testing of viruses involved in pharyngeal ulcers demonstrated the presence of severe acute respiratory syndrome – coronavirus type 2 (SARS-CoV-2) RNA, together with herpes simplex virus 1 DNA. Histopathologic analysis demonstrated full-thickness lympho-monocytic infiltration (mainly composed of CD68-positive cells), with hemorrhagic foci and necrosis of both the mucosal layer and deep skeletal muscle fibers. Fibrin and platelet microthrombi were also found. Cytological signs of HSV-1 induced damage were not found. Cells expressing SARS-CoV-2 spike subunit 1 were immunohistochemically identified in the inflammatory infiltrations. Immunohistochemistry for HSV1 showed general negativity for inflammatory infiltration, although in the presence of some positive cells. Thus, histopathological, immunohistochemical and molecular findings supported a direct role by SARS-CoV-2 in producing local ulcerative damage, although a possible contributory role by HSV-1 reactivation cannot be excluded. From a clinical perspective, this autopsy report of two undiagnosed lesions put the question if ulcers along the GI tract could be more common (but frequently neglected) in COVID-19 patients.